The Unity of the Church and Episcopal Authority in the Thought of Cypriant of Cartage - Yosef Gunawan; Ambrose Naomi Mkyahola (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
This article examines the theological thought of Saint Cyprian of Carthage, one of the third-century Church Fathers, within the context of the Church’s situation in his time, which was marked by profound struggles of faith, particularly the experience of persecution. The focus of the discussion is directed toward the historical and pastoral conditions that shaped Cyprian’s views on the unity of the Church, episcopal authority, and the validity of the sacrament of baptism. Accordingly, this article raises several key questions: What historical background formed Cyprian’s thinking on these three concepts? What were the central ideas he developed regarding ecclesial unity, episcopal authority, and baptism? And how are his ideas relevant to the Church’s teaching, especially in light of the Second Vatican Council? Using a historical and hermeneutical approach, this article traces Cyprian’s life background as well as his pastoral-theological responses to the concrete situations faced by Christians in his time. In the context of the post-persecution crisis, Cyprian played a significant role in addressing internal divisions within the Church, particularly debates concerning the readmission of the lapsi (those who had apostatized). From these struggles, it becomes evident how Cyprian firmly articulated the role of bishops as successors of the apostles and emphasized the sacrament of baptism as the legitimate gateway into ecclesial communion. Based on the historical background of Cyprian’s thought and these three central themes, the article then examines the contribution of Cyprian’s theology to the teachings of the Church as formulated in the Second Vatican Council. Thus, Cyprian’s thought is understood not only as a foundation of early ecclesiology, but also as a living source of faith reflection that remains relevant for the contemporary Church in responding to the dynamics and challenges of the modern age Keywords: Cyprian of Carthage, ecclesiology, unity of the Church, episcopal authority, sacrament of baptism, Second Vatican Council.